Online game-based learning in mathematics education among generation Z: a systematic review - Hidayat, Riyan; Qi, Tay Ying; Tajul Ariffin, Putri Nur’afrina; Mohd Hadzri, Mohamad Hafizullah; Chin, Lin Mei; Ning, Jacqueline Lee Xuan; Nasir, Nurihan (Modestum, 2024)
In contemporary education, game-based learning (GBL) has become a captivating instructional method applied across various academic subjects, including mathematics. The utilization of online GBL in mathematics education constitutes a segment of the activities that mathematics educators can employ during their lessons to teach students and enhance their educational progress. The primary goal of this study was to examine recent research endeavors involving the use of online GBL in mathematics education for Generation Z cohort. To achieve this objective, a systematic review (SR) was carried out to investigate the types of online games employed, analyze previous research methodologies, and explore the educational contexts relevant to mathematics education that align with the needs of Generation Z. An SR process was conducted to gather relevant articles from three databases, namely Science Direct, Scopus, and Springer. Full-text articles were meticulously assessed based on predetermined eligibility criteria. The review revealed many online games suitable for mathematics education, including Augmented Reality, Digital Inquiry Game, E-Rebuild, Math-Island Game, NanoRoboMath, Quizizz, and Wuzzit Trouble. The incorporation of online games in mathematics education offers numerous advantages.